Optimized Balance Between Electricity Load and Wind-Solar Energy Production - Guozden, Tomás; Carbajal, Juan Pablo; Bianchi, Emilio; Solarte, Andrés (Frontiers in Energy Research, 2020)
One of the greatest obstacles in the exploitation of wind and solar resources is the uncertainty in their availability, usually known as intermittence. These effects can be greatly diminished by combining wind and solar resources from different locations. In this article we propose a numerical optimization of future renewable capacity additions aimed to minimize the dispersion of the residual electricity load. Results show that penetration of wind and solar power may increase in another 10% of energy share while keeping the dispersion of the residual load constant, by focusing capacity at sites most correlated with demand cycle. For further increments, an optimized distribution of wind and solar facilities compensates variations between regions. This means that large power additions in solar capacity and wind farms that show positive correlations with the electricity load are compensated by additions in wind farms that are negatively correlated with the annual solar cycle.